A comparison between children with attention deficit/hyperactivity disorder and normal ones in categories of emotional intelligence and attachment styles - Behrouz Behrouz; Shahram Ali Abadi; Fariba Yazdkhasti; Saeed Veisi (Vesnu Publications, 2013)
-